Neutral but not in the middle: cross-cultural comparisons of negative bias of "neutral" emotional stimuli. Issue 6 (17th August 2020) - Tae, Jini; Nam, Ye-eun; Lee, Yoonhyoung; Weldon, Rebecca B.; Sohn, Myeong-Ho
ABSTRACT: Previous studies have shown that the perception of neutral emotion stimuli can be negative rather than absolutely neutral. In the current study, we examined the negative bias of both neutral faces and scenes, cross-culturally between East Asians (e.g. Koreans) and Caucasian Americans. In all experiments, participants performed a Go/No-go task, by either executing or withholding a response toward neutral stimuli presented in the context of positive or negative stimuli. Differentiating neutral stimuli from negative stimuli was less accurate, measured in d', than doing so from positive stimuli. This negative bias was evident with both faces (Experiments 1 and 2) and scenes (Experiment 3). In all experiments, while both ethnic groups demonstrated significant negative biases, there was a subtle modulation of the bias by cultural background. For example, for Korean faces and IAPS scenes, Koreans showed a mitigated negative bias and Caucasian Americans demonstrated a greater negative bias. However, for Caucasian faces, bias was comparable between the two groups. With the possibility of cultural modulation, the prevalent negative bias of neutral emotion questions the validity of the neutrality assumption of the neutral emotion. The study discusses the necessity of methodological and theoretical reconsiderations for the utilisation of neutral emotion stimuli.